Sweat rate and sodium loss during work in the heat - Bates, Graham; Miller, Veronica (Biomed Central, 2008)
Significant and poorly documented electrolyte losses result from prolonged sweating. This study aimed to quantify likely sodium losses during work in heat. Male subjects exercised in an environmental chamber on two consecutive days in both winter and summer. Sweat collecting devices were attached to the upper arms and legs. Sweat rates were higher and sodium concentrations were lower in the summer (acclimatised) than the winter (unacclimatised) trials. Sweat sodium concentration was reduced on the second day in summer but not winter. Regional differences were found in both seasons. The difference between days in summer probably reflects short-term acclimation. The difference between seasons reflects acclimatisation. The data predict average sodium (Na) losses over a work shift of 4.8-6 g, equivalent to 10-15 g salt (NaCl). Losses are potentially greater in unacclimatised individuals. Fluid and electrolyte losses resulting from prolonged sweating must be replaced to prevent imbalance in body fluids, however guidelines for this replacement are often conflicting. This study provides important information for occupational health practitioners by quantifying the likely sodium losses over a work shift and providing recommendations for replacement.